A modified asymptotic method for a Van-der-Pol oscillator with large cubic restoring nonlinearity - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 2004)
A modified asymptotic method is proposed and applied to evaluate the frequency of self-excited oscillation in a Van-der-Pol oscillator with large cubic restoring nonlinearity. The result obtained can be used for large enough nonlinearity.